Mean field homogenization and experimental investigation of short and long fiber reinforced polymers. Issue 1 (October 2016) - Kehrer, Loredana; Pinter, Pascal; Böhlke, Thomas
Abstract: The effective elastic material properties of short fiber reinforced polypropylen are determined by means of the self‐consistent (SC) method and the interaction direct derivative (IDD) method. In order to account for thermoelastic effective material properties, a Hashin‐Shtrikman (HS) based two‐step homogenization method with variable reference stiffness is used. The influence of the reference stiffness, dependent on a scalar parameter is investigated. Information on the microstructure are derived by computed tomography scans (µCT) and considered within the homogenization schemes. Thermomechanical properties of a long fiber reinforced polymer (LFRP) and a short fiber reinforced polymer (SFRP) are obtained by means of dynamic mechanical analysis (DMA). Simulation results for SFRP are compared to experimental results. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)